An approach to energy efficient lighting design for economic residential flats. Issue 1 (November 2021) - Das, Subhasish; Mondal, Anubrata; Ghosh, Kamalika
Abstract: The lighting design in a residential building now-a-days is not only limited to general lighting but also it is focused to provide quality lighting with the help of wide range of available luminaire with different orientations as well as colours with efficient use of energy, that opens up accurate characteristics of specific areas in any room of the building. The affordable housings in many states are some of the examples of residential building where most of the flats in a typical floor are using conventional lighting systems which are not energy efficient and light level is low compared to standards. This paper is mainly focused to provide a budget friendly as well as energy efficient lighting design with the help of new and energy efficient lamps using DIALux Software, which can be proposed to renovate the existing conventional lighting systems. In this paper effort has been made to reduce the power consumption in all rooms and lux levels has been achieved as per standard values along with good amount of energy saving with the use of newer technologies.